The Role of Artificial Intelligence in Modern Drug Discovery and Development - Veeresh Kumar Rathour,; Chitransh Saxena,; Mukul Kumar,; Hemant Brijay, (Asian Journal of Pharmaceutical Research and Development, 2025)
Drug research and discovery have been completely transformed by artificial intelligence (AI), which has improved the precision and efficiency of crucial procedures. Conventional medication development is frequently risky, expensive, and slow. From target discovery to clinical trial design, artificial intelligence (AI) can speed up several phases of drug development with machine learning (ML) and deep learning (DL) algorithms. Early on, the identification of new therapeutic targets is made possible by AI models' ability to forecast possible drug-target interactions. Additionally, by evaluating enormous chemical databases to determine which molecules are most likely to display the necessary biological activity, AI optimizes lead discovery by facilitating high-throughput screening of compounds. AI is also essential for drug repurposing, which is the process of finding new therapeutic uses for already-approved medications. AI can improve safety profiles by identifying trends in patient data that can be used to forecast unfavorable drug interactions. Furthermore, more precise in silico modeling is made possible by AI-driven simulations, which eliminates the need for expensive and time-consuming laboratory testing. AI-enabled clinical trials further improve result prediction, patient monitoring, and patient selection. AI can predict efficacy, find appropriate trial candidates, and expedite trial design by examining genomic data and electronic health information. The article explores how artificial intelligence (AI) is revolutionizing the entire drug development process, stressing both its present uses and its potential to change the pharmaceutical sector in the future and eventually result in the quicker and more affordable creation of new treatments.